(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
Sex abuse in the USA leads the church to the bankruptcies and lost her credibility because the priests have mismanaged their authority for their own interests. The faithful are angry to the hierarchy, seeing that most of the victims are children under age, and they do not have any power to escape from the abusive relationship. The church in Indonesia should learn from the cases in the USA, and prepares the Indonesian priests and all people working in the Church to apply the ethical conducts of profession.